2019
DOI: 10.2196/15018
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Chatbot “Vivibot” to Deliver Positive Psychology Skills and Promote Well-Being Among Young People After Cancer Treatment: Randomized Controlled Feasibility Trial

Abstract: Background Positive psychology interventions show promise for reducing psychosocial distress associated with health adversity and have the potential to be widely disseminated to young adults through technology. Objective This pilot randomized controlled trial examined the feasibility of delivering positive psychology skills via the Vivibot chatbot and its effects on key psychosocial well-being outcomes in young adults treated for cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
179
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(209 citation statements)
references
References 54 publications
7
179
0
Order By: Relevance
“…Using an identical search strategy, we updated this review in January 2020 and identified a further 11 studies. Similar to the previous review, most recent studies were aimed at mental health self-management (n=5) [ 10 - 12 ]. Single studies (n=3) used virtual assistants to provide patients with education and support for breast cancer [ 13 ], genetic counseling [ 14 ], and clinician training [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using an identical search strategy, we updated this review in January 2020 and identified a further 11 studies. Similar to the previous review, most recent studies were aimed at mental health self-management (n=5) [ 10 - 12 ]. Single studies (n=3) used virtual assistants to provide patients with education and support for breast cancer [ 13 ], genetic counseling [ 14 ], and clinician training [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mental health, chatbots are already emerging as useful tools to provide psychological support to young adults undergoing cancer treatment [ 15 ]. However, literature investigating the effectiveness and acceptability of chatbot surveys in health care is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Digital health is rapidly nascent, and a variety of future perspectives need considerations. First, the most important direction that needs to be tackled is the use of (i) chatbots using artificial intelligence and machine learning rather than decision trees, (ii) embodied conversational avatars, or even (iii) hackathons that have the potential to increase patients' therapy adherence, responsiveness, beneficial behavioral patterns, and social interactions to overcome depression and to pave the way to personalized medicine in mental health (49)(50)(51)(52)(53)(54)(55)(56)(57). Second, objective outcome measurements are important to emphasize the beneficial effect of online therapy trials using neuroimaging, e.g., diffusion tensor imaging and functional magnetic resonance imaging, which can help to elucidate microstructural changes in the white matter tracts of the interhemispheric and frontalsubcortical neural circuits that are impaired in depression (58), or to depict the striatal hypoactivation of the reward neuronal network within unipolar depression when anticipating and consuming rewards (59), or epigenetic and modifiable factors, e.g., the dense DNA methylation status of the glucocorticoid receptor gene (NR3C1), which is associated with early life stress and disposes to major depression disorder (60).…”
Section: Future Perspectivesmentioning
confidence: 99%